Analysis Types of Code Mixing used from the Ruang Sandi Podcast Video with Cinta Laura - Prameswari, Dinda Fitri; Angelin, Sheva; Tsalits, Widya Nabbila (English Language and Literature, 2024)
This research focuses on Code Mixing Analysis in Sandi's Podcast with Cinta Laura. This research purposes to describe the types of code mixing and its occurrence. The method of this research is descriptive qualitative analysis to analyze the data. The research data collected from Sandi's YouTube channel entitled Podcast Room with High Motivation Love Achieves Many Things at a Young Age, Sandi Uno "LUAR BIASA!". The study results were described in a video of 18.13 minutes, and researchers wrote down as many as 72 code mixes. The most dominant code mix occurs with the insertion type, which has 41 code mixes. Sandi and Cinta Laura are bilingual because they can speak two languages. This research also shows that Cinta Laura is the one who more often uses code mix from Indonesian into English, and it can be concluded that code mix occurs in every native speaker to communicate.